Alternatives for welfare : (Cambridge University Press, 2003)
This comprehensive survey of key welfare policy issues, in an age of globalization and ageing populations, draws on comparative OECD data and case studies from Scandinavia. Torben Andersen and Per Molander provide a forceful analysis of the main challenges to the traditional public sector welfare state and explore the principal policy options open to governments in advanced economies. They assess the advantages and disadvantages of alternative welfare regimes with less reliance on public sector involvement.